Analisis Mikroplastik pada Sedimen di Perairan Tamalate Kecamatan Galesong Utara Kabupaten Takalar - Kabangnga, Arnold; Islamiati, Dian; Tamti, Hartati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
The existence of microplastics will cause the environment to be disturbed because of their microscopic size so organisms very easily swallow them. This research aims to analyze the microplastic content in sediment based on type, color, shape, size, and type of microplastic polymer. The research method used is quantitative with a survey approach. Sampling was conducted using transects stretched along the coastline for 25m into the sea. Observations at each location consisted of 3 sub transects with 2 repetitions. The research results show that the forms of microplastic found in North Galesong waters are in the form of lines and fragments. A total of 2 particles are in the form of fragments and 41 are in the form of lines. Analysis of the color of the microplastics found 27 particles blue, 7 particles transparent, 8 particles red, and 1 particle green. The size of microplastics at station 1 was dominated by line shapes with sizes ranging from 0.084-0.854 mm and those in fragment form ranging from 0.222 mm, at station 2 the size of line shape microplastics ranged from 0.069-0.963 mm and fragments 0.092 mm, and at station 3 the microplastic particles were in the form of lines range from 0.063-0.693 mm. The total abundance of microplastics in North Galesong waters was 0.43 particles/gr, namely at station 1 as much as 0.11 particles/gr, station 2 as much as 0.11 particles/gr, and station 3 as much as 0.21 particles/gr. The types of polymers found at each station are polyester polymer, PAN film, isotactic polypropylene, powdered cellulose, cellulose, and cellophane.